Optimization and Evaluation of Conditions for Orthotopic Nude Mouse Models of Human Liver Tumor Cells - MENG Yu; LIANG Dongli; ZHENG Linlin; ZHOU Yuanyuan; WANG Zhaoxia (Shiyan dongwu yu bijiao yixue)
Objective The study aims to optimize the conditions for constructing orthotopic nude mouse models of liver cancer by injecting human liver tumor cell lines and to explore appropriate timings for drug administration. Methods Human hepatocellular carcinoma Hep3B and hepatoblastoma HepG2 cell lines, which stably expressing the luciferase reporter gene (LUC), were selected. The linear correlation between the luciferase luminescence intensity and the number of liver tumor cells was analyzed using a Small Animal In Vivo Imaging system to verify the luminescent efficiency of the human liver tumor cells. Different concentrations (8×106, 2.4×107, 7.2×107 cells/mL) and resuspension media (PBS, Matrigel) of human liver tumor cell suspensions HepG2-LUC and Hep3B-LUC were orthotopically inoculated into the liver lobes of 5-week-old female BALB/c nude mice (12 groups, 7 mice each) to construct human liver tumor nude mouse orthotopic cancer models. Every 7 days, the weights of mice were recorded, and the growth of orthotopic tumors was monitored using the Small Animal In Vivo Imaging system. On day 35 post-cell inoculation, mouse livers were dissected, and pathological slices were prepared for HE staining to observe histopathological changes in liver tissues. Results The luminescence intensity of human liver tumor cell lines was positively correlated with the number of cells (R2=0.983 1, R2=0.970 5), indicating their suitability for orthotopic model construction. Successful modeling was achieved in the high-concentration groups of HepG2-LUC, the low-, medium-, and high-concentration groups of HepG2-LUC+Matrigel, the medium- and high-concentration groups of Hep3B-LUC, and the low-, medium-, and high-concentration groups of Hep3B-LUC+Matrigel. For both HepG2-LUC+Matrigel and Hep3B-LUC+Matrigel groups, mice in the high-concentration groups exhibited significantly reduced body weight compared to the low- and medium-concentration groups (both with P<0.05). The luminescence intensity of successfully modeled mice increased exponentially over time (R2>0.950 0), and reached a minimum of 1.0×107 p/(s·cm²·sr) by day 14 post-transplantation. Mice in the low- and medium-concentration groups of HepG2-LUC and the low-concentration group of Hep3B-LUC showed no significant pathological changes, while the other groups exhibited evident liver tumors and hepatocyte lesions. Conclusion For the HepG2-LUC cell line, the recommended injection volume is 50 µL with a cell density of 2.4×107 cells/mL, resuspended with Matrigel, followed by drug administration or prognostic measures on day 7 post-modeling. For the Hep3B-LUC cell line, the recommended injection volume is 50 µL with a cell density of 7.2×107 cells/mL, not resuspended with Matrigel, with administration or prognostic measures on day 14 post-modeling.